The Comparison of Diagnostic Measurements Using Two Different Three-Dimensional Digital Orthodontic Model Software Systems - Nalçaci, Ruhi; Aydin, Burcu; Çokakoglu, Serpil; Biçakçi, Ali Altug; Orhan, Hikmet (The Journal of Dentists, 2017)
Objective: The purpose of this study was to evaluate and compare the reliability and accuracy of diagnostic measurements performed using two different three-dimensional (3D) digital orthodontic model software systems. Materials and Methods: The dental casts of 20 patients with permanent dentition were selected and scanned with an orthodontic 3D scanner (3Shape R700, Copenhagen, Denmark). Two different digital model software programs, Orthomodel (v.1.01, Orthomodel Inc., Istanbul, Turkey) and O3DM (v.2.0, O3DM Thunoegade, Aarhus C, Denmark) were used for diagnostic measurements including tooth width, Bolton discrepancies, intermolar and intercanine distances. A total of 34 measurements were calculated on each digital model. All measurements were repeated by the same observer over 10 randomly selected dental casts at least two weeks later for intraobserver reliability. Results were analyzed statistically. The paired samples t-test was used to compare the differences between the measurements obtained with both softwares. The intraobserver reliability was determined using Cronbach’s alpha test. Results: Cronbach’s alpha value indicated a very high level of reliability for all measurements. Orthomodel and O3DM software programs showed significant differences in the mesiodistal widths of some teeth and the sum of maxillary 6 teeth widths (p<0.05), but not in the Bolton ratios and transverse arch width measurements. Conclusions: Both digital model softwares demonstrated clinically acceptable measurements despite of the differences in some measurements essential for diagnosis and treatment planning.